Tazkiyah Al-Nufūs: Taṣawwuf Akhlāqī Analysist In Building An Ideal Household - Hafizh, Muhammad; M. Mujib Hidayat (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
There exists a research problem concerning the inability of the Muslim community in North Sumatra, Indonesia, to prevent and minimise disputes between husband and wife, despite the presence of taṣawwuf akhlāqī theory as a potential solution to social issues. Through the use of a qualitative literature review, this study synthesises primary and secondary data from scholarly works published within the last decade, employing a descriptive–causal approach through taṣawwuf akhlāqī analysis to understand the development of the ideal family. The research aims to explore the concept of the ideal family and to analyse family disputes through taṣawwuf akhlāqī within the context of household development. The findings indicate that an ideal family relationship is embodied in the concepts of sakīnah, mawaddah, and raḥmah, which aim to produce a golden generation with sound spirituality and positive morality. The results demonstrate that taṣawwuf akhlāqī is crucial for achieving an ideal family relationship and strengthening family resilience. Takhallī helps to minimise negative behaviours that may lead to family conflict, whereas taḥallī enhances positive conduct, enabling families to receive blessings and mercy from Allah SWT. Consequently, family conflicts are reduced, and a golden generation with strong spiritual and moral character can be nurtured as ʿamal jāriyah for the parents who have raised and guided them (tajallī). The novelty of this research lies in the integration of taṣawwuf akhlāqī teachings into the development of the ideal Islamic family through the three stages is takhallī, taḥallī, and tajallī as a comprehensive ethical–spiritual model for building modern household harmony that is both applicable and contextual.